Memantine Effects on Electroencephalographic Measures of Putative Excitatory/Inhibitory Balance in Schizophrenia - Molina, Juan L.; Voytek, Bradley; Thomas, Michael L.; Joshi, Yash B.; Bhakta, Savita G.; Talledo, Jo A.; Swerdlow, Neal R.; Light, Gregory A. (Biological psychiatry : cognitive neuroscience and neuroimaging, 2020)
Abnormalities in cortical excitation and inhibition (E/I) balance are thought to underlie sensory and information processing deficits in schizophrenia. Deficits in early auditory information processing mediate both neurocognitive and functional impairment and appear to be normalized by acute pharmacologic challenge with the NMDA antagonist memantine (MEM). Thirty-six subjects with a diagnosis of schizophrenia and 31 healthy control subjects underwent electroencephalographic recordings. Subjects ingested either placebo or MEM (10 or 20 mg) in a double-blind, within-subject, crossover, randomized design. The aperiodic, 1/f-like scaling property of the neural power spectra, which is thought to index relative E/I balance, was estimated using a robust linear regression algorithm. Patients with schizophrenia had greater aperiodic components compared with healthy control subjects (p < .01, d = 0.64), which was normalized after 20 mg MEM. Analysis revealed a significant dose × diagnosis interaction (p < .0001, d = 0.82). Furthermore, the MEM effect (change in aperiodic component in MEM vs. placebo conditions) was associated with baseline attention and vigilance (r = .54, p < .05) and MEM-induced enhancements in gamma power (r = −.60, p < .01). Findings confirmed E/I balance abnormalities in schizophrenia that were normalized with acute MEM administration and suggest that neurocognitive profiles may predict treatment response based on E/I sensitivity. These data provide proof-of-concept evidence for the utility of E/I balance indices as metrics of acute pharmacologic sensitivity for central nervous system therapeutics.